2007
DOI: 10.1098/rsif.2007.1265
|View full text |Cite
|
Sign up to set email alerts
|

Correlating cell morphology and osteoid mineralization relative to strain profile for bone tissue engineering applications

Abstract: A number of bone tissue engineering strategies use porous three-dimensional scaffolds in combination with bioreactor regimes. The ability to understand cell behaviour relative to strain profile will allow for the effects of mechanical conditioning in bone tissue engineering to be realized and optimized. We have designed a model system to investigate the effects of strain profile on bone cell behaviour. This simplified model has been designed with a view to providing insight into the types of strain distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…At day 7, cell morphology on Chi coatings are spindle with thin pseudopods and prolonged thread-like morphology; however, cells on nanotopographical MBGN-0.50 composite coatings are dumbbell-like in shape during spreading. These cell morphologies indicate the fully differentiated osteoblasts embedded in the bone matrix . Previously, we have reported that presence of small amount of BGN in coatings significantly improved the in vitro apatite-forming ability and osteogenic differentiation …”
Section: Resultsmentioning
confidence: 60%
“…At day 7, cell morphology on Chi coatings are spindle with thin pseudopods and prolonged thread-like morphology; however, cells on nanotopographical MBGN-0.50 composite coatings are dumbbell-like in shape during spreading. These cell morphologies indicate the fully differentiated osteoblasts embedded in the bone matrix . Previously, we have reported that presence of small amount of BGN in coatings significantly improved the in vitro apatite-forming ability and osteogenic differentiation …”
Section: Resultsmentioning
confidence: 60%
“…The authors have designed a model system to investigate the effects of strain profile on bone cell behaviour within a pore. This simplified model has been designed with a view to providing insight into the types of strain distribution occurring across a single pore of a scaffold subjected to perfusion compression conditioning [25]. These studies demonstrated a direct correlation between stress applied and the mineralization of the matrix surrounding the cells within a pore.…”
Section: Compression Systemsmentioning
confidence: 99%